2017
DOI: 10.2217/nnm-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Nanoparticles: A Budding Tool for Cancer Treatment

Abstract: CancerCancer is one of the most incurable diseases and is a major cause of death worldwide. It is estimated that the annual number of deaths due to cancer will be around 13.2 million by 2030 in all over the world [1]. Although chemotherapy is one of the mainstays for its treatment, the side effects as well as disadvantages, such as, normal cell cytotoxicity, chemoresistance and the ability to prevent the occurrence of cancers have been considered as important hitches. Thus, the complementary and alternative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, the clinical application of Ginseng phytochemicals is significantly hampered due to its limited solubility, low oral bioavailability and nontargeted cytotoxicity to normal cells. Most reported nanoparticles of ginsenoside by various nanocarriers, such as polymer-drug conjugates, liposomes and metal nanoparticles could be a promising candidate against cancer and various other diseases [45]. In this study, we found that nanoparticle-like EVs are extracted from P. ginseng root.…”
Section: Discussionmentioning
confidence: 56%
“…However, the clinical application of Ginseng phytochemicals is significantly hampered due to its limited solubility, low oral bioavailability and nontargeted cytotoxicity to normal cells. Most reported nanoparticles of ginsenoside by various nanocarriers, such as polymer-drug conjugates, liposomes and metal nanoparticles could be a promising candidate against cancer and various other diseases [45]. In this study, we found that nanoparticle-like EVs are extracted from P. ginseng root.…”
Section: Discussionmentioning
confidence: 56%
“…However, the outcomes of these therapeutic strategies, mainly exerting pro-apoptotic effects on cancer cells, often ironically cause increased mortality due to the subsequent drug resistance and to metastatic recurrence [ 3 ]. Therefore, increasing attention has been paid to complementary and alternative medicines that take advantages of the medicinal and functional dietary herbs or phytochemicals to concertedly fight against cancers [ 4 ]. Cumulative evidence has pointed out that pterostilbene ( trans -3,5-dimethoxy-4-hydroxystilbene, PS), a dimethylated analog of resveratrol [ 5 ], has excellent pharmacological benefits for the prevention and treatment for various types of cancer by evoking apoptosis or apoptosis-independent effects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of therapeutic strategies such as these have ironically resulted in increased mortality due to drug resistance and metastatic recurrence. Therefore, more attention has been paid to the development of medicinal and functional dietary herbs or phytochemicals as alternatives to medicines to fight cancer (2, 3). Phytochemical agents have often been utilized as alternative therapies to improve the outcomes of traditional cancer treatment.…”
Section: Introductionmentioning
confidence: 99%